2008
DOI: 10.1016/s1472-6483(10)60240-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective vitrification of euploid oocytes markedly improves survival, fertilization and pregnancy-generating potential

Abstract: Enthusiasm for oocyte cryopreservation has been limited by poor pregnancy rates per thawed metaphase II (MII) oocytes (<4%) and low implantation rates per embryos. The reasons relate to technical limitations in the freezing process, and the fact that <40% of oocytes are euploid and unable to produce 'competent' embryos. Comparative genomic hybridization was performed on the first polar body (PB-1) of 323 MII oocytes retrieved from 16 donors. Of these, 111 were euploid, and were vitrified. Seventy-five of 78 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Comparative genomic hybridization has also recently gained attention as a potential means to enhance the selection of embryos used for transfer in the IVF setting (2,3). We recently reported (4,5) on two separate studies where CGH was performed on first polar bodies (PB1) to identify euploid oocytes. In the first study, chromosomal euploidy of PB1 DNA from metaphase II (MII) oocytes was the primary determinant of embryo competence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative genomic hybridization has also recently gained attention as a potential means to enhance the selection of embryos used for transfer in the IVF setting (2,3). We recently reported (4,5) on two separate studies where CGH was performed on first polar bodies (PB1) to identify euploid oocytes. In the first study, chromosomal euploidy of PB1 DNA from metaphase II (MII) oocytes was the primary determinant of embryo competence.…”
mentioning
confidence: 99%
“…In the second study, we selectively vitrified and cryobanked euploid (CGH-normal) oocytes (5). The subsequent transfer of %2 blastocysts derived from such warmed oocytes resulted in a 61% IR per blastocyst, a 75% BR following blastocyst transfer, and a 26% birth rate per warmed oocyte (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies using mouse oocytes and zygotes also showed that microinjected trehalose at its effective concentrations was non-toxic and quickly eliminated during embryonic development [15,29]. In recent years, several studies reported excellent survival rates after vitrification of human oocytes [6,9,[32][33][34]. These results are encouraging; yet the vitrification procedure used in these studies requires direct contact with LN2, and thus is of concern due to contamination risk.…”
Section: Discussionmentioning
confidence: 92%
“…Since the first pregnancy achieved with a vitrified/warmed human oocyte [83] and the first birth of a healthy baby [84], vitrification results have improved significantly during the last decade [17][18][19][20][21][22][23][24][25][26][85][86][87][88]. Vitrification is the glass-like solidification of a solution at low temperature, without ice crystal formation.…”
Section: Discussionmentioning
confidence: 99%